Implementasi Media Big Book dalam Meningkatkan Literasi Membaca Siswa Sekolah Dasar - Nurjani, Nurjani; Adlani, Nazri; Suwarno, Suwarno (WASIS : Jurnal Ilmiah Pendidikan, 2024)
The aim of this research is to hone the reading literacy skills of third grade students at Al-Azhar Muhammadiyah Simabur Islamic Elementary School using big book media. It is hoped that in the future, students will not only read but will be able to derive meaning from the reading material they read. Therefore, it is necessary to arouse students' interest in reading first.Classroom Action Research (CAR) is a research method carried out, there are four PTK steps applied in this research, namely, planning, implementation, observation and reflection. Then the research instruments applied in this research were observation, tests and interviews. Moving on to the data analysis applied in this research, namely qualitative and quantitative.Based on research conducted, there was a discovery that the implementation of big book media could improve students' reading literacy skills, as evidenced by an increase in students' reading literacy skills from cycle 1 to cycle 2. In cycle 1, students' reading literacy reached a class average of 70.7 and students those who have completed and those who have not completed both get a percentage of 50%, consisting of 10 students each. Then in cycle 2 there was an improvement, it can be seen that the class average was 79.15. 90% of students who completed their studies consisted of 18 students, and 10% of those who did not complete their studies consisted of 2 students. This proves that big book media can improve students' reading literacy skills well.